Age-stratified associations between radiotherapy and SPMs for FPHNC: a population-based cohort study - Yuan-Yuan Li; Qiong Liu; Si-Qi Ying; Xiu-Quan Wu; Xiao-Hui Zhang; Xiao-Mei Xie; Bing-Dong Sui; Yan Jin; Yang Jiao; Franklin R. Tay (Military Medical Research)
Abstract Background Second primary malignancies (SPMs) account for over 30% of total deaths in head and neck cancer (HNC) patients. The increasing use of radiotherapy raises concerns about the elevated risk of radiation-associated SPMs. This study aimed to investigate the age-stratified association between radiotherapy and SPM risk in survivors of non-metastatic primary HNC. Methods Using data from the Surveillance, Epidemiology, and End Results program (2004−2015), incidence rate ratios (IRRs) and standardized incidence ratios (SIRs) were evaluated for solid and hematologic SPMs associated with radiotherapy within different age groups. Follow-up for hematologic and solid SPMs began 2 and 5 years, respectively, after the diagnosis of first primary HNC. The IRRs for SPMs were compared between radiotherapy-exposed and unexposed groups using multivariable modified Poisson regression. The SIRs were computed as the ratio of observed cancers in the cohort to expected cases derived from sex-, age-, and calendar year-matched general population incidence rates. Results The study included 75,209 2-year survivors, with 73.2% being male and a median age of 60 years. Of these, 58,063 had survived 5 years or more. Radiotherapy was associated with an increased risk of solid SPMs [IRR = 1.16, 95% confidence interval (CI) 1.08−1.24; P < 0.001]. The associations varied significantly among young (aged 15−39 years), middle-aged (aged 40 − 64 years), and elderly (aged 65−89 years) patients. Specifically, radiotherapy was associated with an increased risk of solid SPMs in middle-aged patients (IRR = 1.21, 95% CI 1.11−1.32; P < 0.001), and a decreased risk of hematologic SPMs in elderly patients (IRR = 0.77, 95% CI 0.60−0.99; P = 0.045). Compared with the general population, young patients had an elevated risk of radiotherapy-associated second primary non-Hodgkin lymphoma (SIR = 4.01, 95% CI 1.47−8.74). Middle-aged patients showed the highest SIR for SPMs in the bones/joints (SIR = 7.72, 95% CI 4.32−12.73), while elderly patients had the highest SIR for second primary esophageal malignancies (SIR = 3.87, 95% CI 2.91−5.05). Males were more likely to develop solid SPMs compared to females. Conclusions This study reveals an age-stratified association between radiotherapy and the risk of SPMs in HNC patients. These findings highlight the importance of considering patient age when making treatment decisions for HNC and suggest that long-term surveillance is necessary for high-risk groups.